閉塞性睡眠時無呼吸症候群に対する口腔内装置治療の有用性に関する検討 - 内田, 文彦; 馬場, 脩; 長谷川, 正午; 伊藤, 寛之; 柳川, 徹; 佐藤, 誠; 菅野, 直美; 武川, 寛樹; 鬼澤, 浩司郎; 山縣, 憲司 (日本口腔外科学会雑誌, 2016)
A clinical study was performed in patients with obstructive sleep apnea syndrome (OSAS) to clarify the effectiveness of an oral appliance (OA). In 40 patients, the mean apnea hypopnea index (AHI) was 24.7 ±19.3 /h at baseline, and they were classified into 13 mild (AHI 5 to <15), 18 moderate (AHI 15 to <30) and 9 severe (AHI ≥30) cases of OSAS. The AHI on OA therapy decreased significantly (P<0.0001) to a mean AHI of 5.9±5.1/h, and the improvement rate was 71.0±28.0%. Twenty-one patients (52.5%) had a successful response (AHI <5). There was no significant difference in the AHI on OA therapy among the mild, moderate, and severe groups. The AHI improvement rate was low (51.7%) in patients with a body mass index (BMI) of ≥25 kg/m2; however, there was no significant difference in the AHI improvement rate on covariance analysis assuming that BMI was a covariate. Therefore, the effect of OA did not depend on the BMI. There was no significant difference in the reduction in AHI among groups classified according to age or Epworth sleepiness scale (ESS). These results suggested that OA therapy was effective for mild and moderate OSAS cases and that improvement in AHI can be expected in severe OSAS or obese patients.